Prognostic and clinicopathological value of dbc1 expression in human cancers: a systematic review and meta-analysis - Wang, Haojia; Cheng, Xinhong; Zhang, Bruce Xianzhuo; Wang, Yong; Gao, Shuo; Ding, Fanghui; Song, Xiaojing; Li, Dandan; Ni, Haixu; Luo, Yang; Li, Xun (Frontiers in Oncology, 2025)
BackgroundDBC1 is a large nuclear protein that is thought to influence the development of several human cancers. However, further research has revealed that the relationship between DBC1 and the prognosis and pathological characteristics of cancer patients is controversial. The aim of this paper is to explore the significance of DBC1 in cancer through the method of meta-analysis.MethodsA systematic search of the PubMed, Web of Science, Embase, CNKI, and Wanfang databases was conducted, resulting in the identification of 25 studies encompassing 4014 patients. The Hazard Ratio (HR) and ratio ratios (RR) were combined using STATA 14.0 software, and 95% confidence intervals (CI) were obtained to assess the association of DBC1 with prognostic and pathologic characteristics of cancer patients.ResultsMeta-analysis of the combined results demonstrated that patients with cancer who exhibited DBC1 overexpression exhibited shorter overall survival (OS) (n = 17, HR = 1.948, 95%CI: [1.280-2.964], P = 0.002, I2 = 88.6) and recurrence-free survival (RFS) (n = 11, HR = 2.182, 95%CI: [1.430-3.330], P = 0.000, I2 = 87.8) rates. In terms of pathological features, elevated DBC1 expression was indicative of poor TNM stage (n = 23, RR = 1.245, 95%CI: [1.012-1.531], P = 0.038, I2 = 79.3), distant metastasis (n = 11, RR = 1.987, 95%CI: [1.021-3.866], P = 0.043, I2 = 63.8), and histologic grade (n = 18, RR = 1.433, 95%CI: [1.115-1.843], P = 0.005, I2 = 79.2).ConclusionDBC1 overexpression is associated with poor survival cycle and pathologic features in cancer patients, and it has the potential to be a predictive prognostic marker for cancer. However, more high-quality prospective studies are still needed to validate our conclusions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023426104.